2020
DOI: 10.1186/s12876-020-01430-9
|View full text |Cite
|
Sign up to set email alerts
|

A case report of pancreatic panniculitis due to acute pancreatitis with intraductal papillary mucinous neoplasm

Abstract: Background: Pancreatic panniculitis is a rare skin manifestation in pancreatic disease patients that most frequently develops on the lower legs. We report the unique case of a 68-year-old man who suffered from pancreatic panniculitis on his trunk associated with acute pancreatitis due to an intraductal papillary mucinous neoplasm. Case presentation: A 68-year-old man complained of a 2-day history of a tender subcutaneous nodule on his trunk. Laboratory tests and abdominal contrast computed tomography were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Polyarthritis and pancreatic panniculitis associated with pancreatic carcinoma [16][17][18][19][20][21] Acinar cell carcinoma of the pancreas…”
Section: Paraneoplastic Arthritis Malignant Neoplasmsmentioning
confidence: 99%
“…Polyarthritis and pancreatic panniculitis associated with pancreatic carcinoma [16][17][18][19][20][21] Acinar cell carcinoma of the pancreas…”
Section: Paraneoplastic Arthritis Malignant Neoplasmsmentioning
confidence: 99%
“…Apart from typical IPMN clinical presentation regarding abdominal symptoms and jaundice, skin lesions named pancreatic panniculitis have been reported. Yamashita et al [ 14 ] described a case of a 68-year-old man presenting pancreatic panniculitis on his trunk coexisted with IPMN-associated AP. A skin biopsy of the lesion histologically showed lobular panniculitis with characteristic "ghost cells" (pancreatic panniculitis).…”
Section: Diagnostics Of Ipmnsmentioning
confidence: 99%
“…A skin biopsy of the lesion histologically showed lobular panniculitis with characteristic "ghost cells" (pancreatic panniculitis). The authors concluded that clinicians should take into account IPMN in patients with in orderto avoid a missed or delayed diagnosis[ 14 ]. Similar cases of AP and IPMN-related panniculitis have also been reported by other authors[ 15 , 16 ].…”
Section: Diagnostics Of Ipmnsmentioning
confidence: 99%
“…Various pancreatic disorders have been associated with panniculitis, namely acute or chronic inflammatory pancreatitis, pancreatic carcinoma of different subtypes and metastatic cancer-causing pancreatic invasion. 5 The pathogenesis remains unclear but is likely to be closely related to the systemic release of pancreatic enzymes-most clearly lipase, followed by amylase and trypsin-resulting in subcutaneous lipolysis. Other proposed mechanisms consider the role of traumatic, infective or trypsin-induced vascular damage, the special lipid conformations in adipocyte cell membranes increasing pancreatic enzyme absorption, adipokine release, immune complex formation and alpha-1antitrypsin deficiency in causing adipocyte necrosis and panniculitis.…”
Section: Pancreatic Panniculitismentioning
confidence: 99%
“…Other proposed mechanisms consider the role of traumatic, infective or trypsin-induced vascular damage, the special lipid conformations in adipocyte cell membranes increasing pancreatic enzyme absorption, adipokine release, immune complex formation and alpha-1antitrypsin deficiency in causing adipocyte necrosis and panniculitis. [5][6][7] Clinically, it presents as erythematous, oedematous, painful nodules on the lower extremities, sometimes on the anterior trunk, arms and scalp. 6 They can occur singly or in crops, with the potential to ulcerate and migrate.…”
Section: Pancreatic Panniculitismentioning
confidence: 99%